Someone to talk to: perspectives on personal discussion networks. An interview with Mario Luis Small - Espinoza, Vicente (AWARI, 2020)
The article presents an interview with Dr. Mario Luis Small about his works and contributions to social network analysis. The conversation revolves around four topics: first, the linkages between his research on urban communities and the current validity of the social capital approach. The second section discusses multiplexity in personal social networks as well as the shortcomings of a deductive approach to this subject. Third, the interview considers the effects of the contexts of interaction for the analysis of discussion networks. The final part of the interview provides recommendations regarding the interpretation of the information obtained from a name generator